EFEKTIVITAS PROGRAM PENDIDIKAN LUAR SEKOLAH DALAM KEJAR PAKET C DI PUSAT KEGIATAN BELAJAR MASYARAKAT “VARIANT CENTRE” KELURAHAN PETEMON KECAMATAN SAWAHAN KOTA SURABAYA - Wiwit Wahyuningtias Anggraini (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2017)
Non formal education is the path of education outside formal education can be structured and tiered. Law No. 20 of 2003 on National Education System Article 26 (1) states that non-formal education organized for citizens who require educational service that serves as a substitute for, or complement formal education in order to support lifelong education. Equitable access to adult education has become a trend (tendency) won the Society Development Index (HDI), which has three inter-related indicators, such as Economy, Education and Health. Therefore, the government tried to pursue programs to improve educational equity, one of which is with the Community Learning Center (CLC). CLC is an institution that has an important role for the Non-Formal Education. This study aims to determine and describe the effectiveness of the implementation of comprehensive school education programs (PLS) in Packet C at PKBM Variant Centre Surabaya also analyze the factors supporting and inhibiting. The research is described by using qualitative research methods and descriptive research, using the technique of collecting data through interviews, observation, and documentation. Determination of informants using purposive and snowball technique. Methods of data analysis include data reduction, data presentation, and conclusion. This study shows that the School Education Program Effectiveness in the Packet C at Community Learning Center Variant Centre is quite effective.